Pelaksanaan Perjanjian Bagi Hasil Pohon Aren terhadap Petani dan Pemilik di Desa Juhar Ginting Sada Nioga - Pinem, Jaya Prana; Barus, Utary Maharani; Isnaini, Isnaini (Mahesa Research Center, 2023)
This study discusses the implementation of palm tree production sharing agreements; what are the legal consequences if one of the parties defaults on the palm tree profit sharing agreement and is there legal certainty for the implementation of the palm tree production sharing agreement in Juhar Ginting Sada Nioga Village based on